The role of the political commissar in activating the military action of the Algerian Liberation Revolution (1956-1962) - Sbihi, Aicha; taouanza, mahfoud (The Algerian Historical Journal, 2026)
The article mainly revolves around the role of the political commissar in activating the military action of the National Liberation Army during the period (1956-1962), bearing in mind that the function of the political commissar emerged from the Soumam Conference of August 20, 1956 AD within the framework of structuring and generalizing the various political and administrative organizations of the revolution, where his tasks were demarcated, which pour into The framework of popular mobilization and ensuring the rallying of the masses around the revolutionary action. Therefore, the roles played by the political conservative were diversified and affected various aspects of the liberation revolution; Including the military aspect, where the political governor had active contributions to it through political education among the National Liberation Army, intelligence work and supervision of recruitment, which reflected positively on the military performance of the mujahideen and gave a strong impetus to the Algerian liberation revolution.